Reconsidering What Nietzsche Meant By The Same In The Doctrine Of The Eternal Recurrence - Strebel, Wilhelm Patrick Joseph S (Archīum Ateneo, 2019)
Hermeneutical considerations involving the nuances of words in translation have a bearing in interpreting philosophical concepts. Stambaugh highlighted the eternal in Nietzsche as well as the meaning of the Same in the doctrine of the Eternal Recurrence of the Same. As translation of the German word das Gleiche, she provided important considerations regarding the nuances of das Gleiche and the sense of how the English word “the same” could capture as well as leave out some meanings in the original. This paper builds on Stambaugh’s observations by providing a linguistic analysis of das Gleiche to open up to how it does mean immediacy and likeness as Stambaugh already observed, but the said analysis propels the discussion further by also pointing to the fact that das Gleiche also refers to what is imminent and forthcoming. This reconsidered meaning of das Gleiche as imminent and open to futurity will provide a fresh understanding of Nietzsche’s doctrine. The paper ends by featuring Higgins’s reading of eternal recurrence as present-oriented akin to the temporal experience of music to show that this insight in Higgins could also be developed further by showing the futurity and imminence of music as hermeneutical key to Nietzsche’s doctrine.